My grandfather would have shot me : a black woman discovers her family's Nazi past - Teege, Jennifer 1970- (The Experiment, 2015)
Umfang und Inhalt: "The memoir of a German-Nigerian woman who learns that her grandfather was the brutal Nazi commandant depicted [by Ralph Fiennes] in Schindler's List, Amon Goeth"--Provided by publisher.